H-Infinity Controller with LMI Region Schemes for a Lab-Scale Rotary Pendulum Crane System - Mohd Zaidi, Mohd Tumari; Muhammad Salihin, Saealal; Yasmin, Abdul Wahab; Mohd Riduwan, Ghazali (Medwell, 2012)
This study presents an H-infinity controller with LMI region schemes for a lab-scale rotary pendulum crane system. H-infinity synthesis with pole clustering schemes is used to control the hub angle of the arm of rotary pendulum crane system with very minimal sway angle. The performance of the lab-scale rotary pendulum crane system is examined in terms of time response specifications of hub angle of the arm, minimal sway angle of pendulum and minimal control input. To examine the effectiveness of the proposed controller, it is compared with LQR controller schemes. The implementation results show that H-infinity controller with confined closed-loop poles based on LMI region produce a fast tracking capability with very minimal sway and control input.